Connected older citizens : ageing in place and digitally mediated care in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Media Studies at Te Kunenga ki Pūrehuroa, Massey University Manawatū, Aotearoa New Zealand - Vonk, Lisa (Massey University, 2025)
Amidst discussions of Aotearoa New Zealand’s ageing population, how to care for growing numbers of older people is a considered a preeminent social and political issue. Digital technologies are imagined to be a particularly desirable solution in contexts where social values of independence intersect with the neoliberal state’s desire to reduce the amount of money spent on medical and social care. There is a substantial market for gerontechnologies (technologies specifically designed for older people) aiming to capitalise on the ‘silver tsunami’. Yet, digital technologies such as smart phones, exercise watches and laptops are widely accessible in Aotearoa New Zealand. They are increasingly used by older people to maintain social connectedness, coordinate practical support, and manage health. The purpose of this research was to explore how this digitally mediated care functions for community-dwelling older people. Taking an innovative theoretical-methodological approach, I combined actor-network theory with political economy theory. This enabled me to robustly examine sociotechnical care networks, paying attention both to the role of technologies in producing care as well as analysing who benefits from older people’s engagements with technology for care. The research draws on interviews with sixteen community dwelling older people, marketing materials of technologies used by those interviewed, the interface of an exchange platform and a patient portal used by some of those interviewed, as well as government documents. This data was analysed using network mapping, thematic analysis, and interface analysis. I ultimately demonstrate that digitally mediated care practices enact a ‘connected older citizen’. Through digitally mediated care practices, older people adjust (and are adjusted) to a culture of connectivity. Digitally mediated care involves new forms of labour. Social connection is framed as a core social value. I argue that digitally mediated self-care redefines independence in terms of the ability to use digital technologies to manage connections to reduce visible dependence on others. Notably, I show the imagined benefits of digitally mediated care are often not realised in practice due to limitations of technologies used in care (such as patient portals). Significantly, the priorities and needs of older people are not often at the forefront of digitally mediated care.
Keywords: actor network theory, culture of connectivity, ageing, digital media, care; Older people; New Zealand; Conduct of life; Communication; Information technology; Social aspects; Technology and older people; Internet and older people; 470102 Communication technology and digital media studies; 520505 Social psychology